Pemberdayaan Ekonomi Rumah Tangga melalui Pelatihan Pembuatan Sabun Cuci Piring di Desa Pejok - Sholahuddin, Moh.; Ulandari, Siti Ayu; Bella, Sinta Nur Salsa; Agustin, Wulan; Prasetyo, Mochammad Dony; Dinanti, Kurnia Trisna; Mukhoffi, Mursyida (Universitas Nusantara PGRI Kediri, 2024)
Training on the process of making dishwashing soap in Kepohbaru District Village was carried out as an effort to address the low skills and income of village communities and as an effort to empower the local economy. This training was attended by 18 participants with the main target being low-income communities and active PKK groups. The purpose of this service is to teach knowledge and skills to the community in producing dishwashing soap, so that it can realize opportunities for new businesses. The methods used in this service include an active participation approach or Participatory Action Research (PAR) and demonstrations, where training is carried out by delivering materials and direct practice. The results of the training showed that participants were able to make dishwashing soap supported by supporting materials such as brochures and modules as a reference for independent dishwashing soap production.